PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Krisnhoe Sukma Danuta; Minadi Wijaya (FEB UNWIKU PURWOKERTO, 2020)
This research was conduct to analyze the effect of managerial ownership, leverage, and audit quality on the financial statements integrity of manufacturing companies listed on the IDX from 2016 to 2018. Purposive sampling method were used as sampling method which results in 35 companies as the sample. Data research analysis using multiple linear regression with the help of SPSS 22. The results showed that leverage has a negative effect on the integrity of financial statements, while managerial leadership and audit quality have no effect on the integrity of financial statements.